Chalcidoidea nova vel minus cognita (Chalcidoidea). - Erdös, József (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication contains the descriptions of a new genus: Pentacladocerus and two new species: Pentacladocerus matranus and Mayridia sachtlebeni, notes on the synonymy of Idarnotorymus pulcher Masi and Prionomitus cleone Walker and remarks on the systematic position and distribution of Coenocerus puncticollis Thomson. Nomenclatural Acts Pentacladocerus Erdös, 1963 (Chalcidoidea), gen. n. Slanecia Bouček, 1955 (Chalcidoidea), syn. n. of Idarnotorymus Masi, 1916 azurea Mercet, 1921 (Eucantabria), syn. n. of Coenocerus puncticollis Thomson, 1875 sachtlebeni Erdös, 1963 (Mayridia), spec. n. matranus Erdös, 1963 (Pentacladocerus), spec. n. elongata Bouček, 1955 (Slanecia), syn. n. of Idarnotorymus pulcher Masi, 1916